(x-2)(x+9) = 7
The difference of a positive number and 2 (x-2)
multiplied times the
sum of the number and 9 (x+9)
x^2 +7x -18 = 7
x^2 +7x -25 = 0
Can you finish from here? You will get a positive and a negative result, but the problem calls for a positive number only.
when the difference of a positive number and two is multiplied by the sum of the number and 9 and the result is 7 find the number
i just need help setting this up i can do the work myself
heres what i did:
9(x-2)=7 but im sure im wrong.
1 answer